Optimization of the process of egg omelet production with fillings with extended storage period - V. Sukmanov; O. Beskrovnyi; O. Malych (Ukrainian Food Journal, 2015)
Introduction. Optimization of the egg omelets (EO) production using high pressure (HP) will allow to produce a minimum cost product during manufacturing and also to obtain a product with high consumer properties. Materialsand methods. The concerned product is -EO -a mixture of liquid egg with grated or chopped cheese, xanthan gum, water or milk and spices. The EO manufacturing process consisted of packing the mixture in an airtight container with heating and processing in the high pressure installation. The EO suitability for long-term storage was evaluated by the "water activity" term. The EO quality was evaluated by an expert. There was used the undetermined Lagrange multipliers method to obtain the optimal process parameters. Results. As a result of the central composite rotatabel plan there was developed optimization model allowed to obtain the optimal EO HP processing parameters: pressure – 690 МPа, temperature –1220С, treatment duration –7×60s, 14g of water on 100 g of melange, 13 g of dry milk on 100 g of melange, xanthan gum content -0,75% of the total mixture mass, 25 g of cheese on 100 g of melange. These indicators allow to obtain the EO process parameters with the next indicators: water activity -0.704 and comprehensive quality Score - 0.98 that characterize the product as a product with high quality indicators stable over a long period of storage. The developed model analysis with using of Student's t test, Fisher dyspepsia and predicted optimization values calculation errors confirmed the reliability of the optimization parameters obtained values and the optimization model reliability. The calculations results for the given optimization parameters are presented as confidence intervals, confirming that their experimental values do not exceed the respective intervals and thus confirm the results authenticity . Conclusions. These results have practical significance and were adopted as the basis for the technical documentation elaboration of the EO long term storage and the HP process equipment design for implementation of this process.